Pemanfaatan Artificial Intelligence (AI) dalam Pembelajaran Kimia di Bandar Lampung - Rosilawati, Ila; Setyarini, M.; Saputra, Bayu; Utami, Gamila Nuri (Jurnal Dehasen Untuk Negeri, 2025)
Chemistry teachers in Bandar Lampung face challenges in using AI in teaching chemistry at school. To overcome this problem, training is needed to facilitate increasing chemistry teachers' understanding of the use of AI in learning. The aim of this training is for chemistry teachers in Bandar Lampung to understand and be able to use AI which can increase learning effectiveness. The method used in this training is to provide direct training both theory and practice, test instruments are used to see improvements in training results. The results of the training had a positive impact, providing significant improvements. The average post-test score is 88, this value is greater than the pre-test score of only 71. This increase is an indication of the success of the training. So that teachers can make learning more effective at school by utilizing technology as an AI-based learning resource. In the end, it can improve the quality of chemistry learning in schools.